2014
DOI: 10.1371/journal.pone.0106932
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome of the Hemimetabolous German Cockroach (Blattella germanica)

Abstract: BackgroundThe German cockroach, Blattella germanica, is an important insect pest that transmits various pathogens mechanically and causes severe allergic diseases. This insect has long served as a model system for studies of insect biology, physiology and ecology. However, the lack of genome or transcriptome information heavily hinder our further understanding about the German cockroach in every aspect at a molecular level and on a genome-wide scale. To explore the transcriptome and identify unique sequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…The biological process terms were primarily associated with cellular processes, such as proteolysis, carbohydrate metabolic processes and oxidation-reduction utilization. Similar compositions and distributions of unigenes assigned to GO terms have been reported in transcriptomics descriptions from other insects [9, 12].
Fig.
…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The biological process terms were primarily associated with cellular processes, such as proteolysis, carbohydrate metabolic processes and oxidation-reduction utilization. Similar compositions and distributions of unigenes assigned to GO terms have been reported in transcriptomics descriptions from other insects [9, 12].
Fig.
…”
Section: Resultssupporting
confidence: 79%
“…A total of 35,430 unigenes with a mean length of 716 bp were obtained from the transcriptome analysis. The average length of the unigenes for ACB in the present study was longer than those observed in Plutella xylostella (532 bp) [15] and Liposcelis bostrychophila (711) [16] but shorter than those in Blattella germanica (798 bp) [9] and Agrotis ipsilon (770 bp) [17]. The length of the unigenes may be related to the sequencing technique and assembly tools used.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Zhou et al. () described partial sequences for 14 OBPs, two ORs, and four GRs from a whole body transcriptome conducted using pyrosequencing, whereas Niu, Liu, Dong, and Dong () expanded the OBP total to 48 mostly complete sequences by performing an antennal transcriptome using ILLUMINA sequencing and also found five ORs and 5 IRs, albeit mostly partial sequences. The sequencing of the B. germanica genome as part of an i5k pilot project (Robinson et al., ; i5k Consortium ) allowed Harrison et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable, in a similar mode as reported for other pest species, that this large proteome allowed B. germanica to evolve such a broad range of resistance to toxins and pathogens. In fact, a de novo transcriptome of B. germanica revealed a large repertoire of transcripts important for the metabolism of toxins and defense against pathogens (Zhou et al., ). These include genes in both the Toll and Imd pathways, including serpins (47), cathepsins (32), lipopolysaccharide‐binding proteins (21), transferrins (20), Gram negative bacteria binding proteins (4), Toll‐like receptors (16), peptidoglycan recognition proteins (15), lysozymes (8), Imd proteins (3), and others including 115 lectin‐like proteins and 18 β‐glucanases (Zhou et al., ).…”
Section: Introductionmentioning
confidence: 99%